Evaluation of US Food and Drug Administration Drug Label Recommendations for Coadministration of Antivirals and Acid‐Reducing Agents. Issue 5 (26th August 2022) - Shugg, Tyler; Powell, Nicholas R.; Marroum, Patrick J.; Skaar, Todd C.; Younis, Islam R.
Abstract : Coadministration with acid‐reducing agents (ARAs), including proton pump inhibitors (PPIs), histamine H2 ‐receptor antagonists (H2 blockers), and antacids has been demonstrated to reduce antiviral exposure and efficacy. Therefore, it is essential that US Food and Drug Administration (FDA) drug labels include recommendations to manage these drug–drug interactions (DDIs). This investigation analyzed information in FDA drug labels to manage DDIs between ARAs and antivirals approved from 1998 to 2019. To ascertain clinical adoption, we assessed whether FDA label recommendations were incorporated into current antiviral clinical practice guidelines. We identified 82 label recommendations for 43 antiviral approvals. Overall, 56.1% of recommendations were deemed clinically actionable, with the most common actionable management strategies being dose adjustment during coadministration (40.2%) and coadministration not recommended (9.8%). The sources informing DDI recommendations were clinical DDI studies (59.8%) and predictions of altered exposure (40.2%). Antivirals with low aqueous solubility were more likely to have label recommendations and were more commonly investigated using clinical DDI studies ( P  < 0.01). For recommendations informed by clinical DDI studies, changes in drug exposure were associated with actionable label recommendations ( P  < 0.01). The frequency of exposure changes in clinical DDI studies was similar across antiviral indications, but exposure changes were numerically higher for antacids (71.4%) relative to PPIs (42.9%) and H2 blockers (28.6%). Of DDI pairs identified within drug labels, 76.8% were included in guidelines, and recommended management strategies were concordant in 90.5% of cases. Our findings demonstrate that current regulatory oversight mostly (but not completely) results in actionable label recommendations to manage DDIs for high‐risk antivirals.